Improving students’ achievement in learning bangun ruang sisi datar by using combination of cooperatif learning approach type of jigsaw and original media items in math subject at the ninth grade students’ in Smp negeri 2 bayang kecamatan bayang - Ermanilis Ermanilis (Jurnal Ilmiah Pendidikan Scholastic, 2018)
This study departs from the background of the need for renewal in the improvement of teachers' creativity in mathematics learning process management on the material side room flat wake of lower secondary education in response to the weakening of the quality of student learning.In learning activities, the subject matter is not contextual, and low student performance, both in the process and products of learning.Most teachers are still implementing learning with traditional learning approaches. The situation is likely to lead to burnout, boredom and lack of interest and motivation of student learning.Based on the description of the above problems, through research is expected the teachers to play a role as an innovator of learning.Increasing teachers' creativity and learning media support the absolute need to be developed. This study used a qualitative approach to obtain data and analysis through studies reflective, participatory, and collaborative.Program development based data and information from students, teachers and classes are naturally social setting through the three stages of the cycle of action research. In order to improve learning outcomes and learning activities of students in the room woke flat side of classroom action research conducted using a combination of cooperative learning approaches and media jigsaw original object.The research was done in class IX SMP Negeri 2 Shaded by three cycles.In the first cycle, the majority of students not yet accustomed to the conditions jigsaw cooperative learning by using media the original object, so that action by explaining to the students about the principles of cooperative learning jigsaw. In the second cycle, students and teachers have started to understand the implementation of cooperative learning jigsaw and showing satisfactory results. From observation result of student activity increase. While the learning outcomes of students geometrical flat side showed an increase from an average of 53 in the first cycle to 79 in the second cycle and 80 cycles third. Mastery learning students also showed an increase of 43% in the first cycle to 87% in the second cycle and 90% in the third cycle of the value of a minimum completeness criteria 60. In terms of implementation of action research, the cycle of the first, second, and third it can be concluded that a combination of approaches cooperative learning jigsaw and original objects media to improve learning outcomes wake flat side room and activity of students in class IX students of SMP Negeri 2 Bayang.